(3GdGOGQI GdHjFjI aj GdLeghQjI GdjefjI heJWdHGJ JWhjQgG hJYRjRgGs - (3YGOd YHO GdQTjO(B, (3YHO GdQRGbs ((3UfYGA(B:s (3OGQ GdcJGH(B,s, 2001)
(3gPG GdcJGH G(B1- (3dGOGQI GdHjFjI (B: (3eaghegG hYdGbGJgG HGdJfejI (B2 - (3GdeTcdGJ GdHjFjI GdQFjSjI aj GdLeghQjI GdjefjI hGfYcGSGJgG Ydi GdJfejI GdGbJUGOjI hGdGLJeGYjI (B3- (3GdGOGQI GdHjFjI aj GdLeghQjI GdjefjI hehbYgG aj GdGOGQI GdHjFjI GdYQHjI (B((3fehPL LeghQjI eUQ GdYQHjI (B)(3GdfJGFL hGdJhUjGJs
Keywords: (3GOGQI GdHjFjIs